A Study of Duration of Oxygen Therapy and Severity of Respiratory Distress in New Born (Indian Journal of Public Health Research & Development, 2021)
Objective: This prospective study was conducted:1. To study the duration of oxygen therapy and severity of respiratory distress in newborn.2. To establish that with increase in severity of distress (Downe’s score) there is increase in duration ofoxygen requirement.Methods: This study was carried out on a total number of 100 newborns including preterm and term newbornwith respiratory distress.Spearman Rank Correlation:Cofficient was used to assess the correlation between Downe’s score and number of days oxygen required.Data analysis was done using statistical package for social sciences(SPSS) Version 22.0.Result: The study shows that 24% the newborn with respiratory distress required O2 treatment for less than24 hours, as compared to the 76% of newborns with respiratory distress (42% for 2 days, 10% for 3 days,3% for 4 days, 21% for 5 days) required O2 treatment for >24 hours. There was no newborn with respiratorydistress that did not required O2 therapy. None of the newborn with TTN required O2 for more than 2 days,7 out of 14 newborn with RDS (50%) and 3 out of 13 newborns with MAS(23.07%) had severe distress andrequired oxygen for more than 24 hours. Bhutta ZA et al studied 81 neonate with respiratory distress andit was seen that these babies required supplemental oxygen while in NICU, but unlike our study, the abovestudy has not analyzed O2 requirement depending on the cause of respiratory distress which should help todetermine clinical outcome.Conclusion: A total of 100 newborns with respiratory distress including term and preterm delivered eitherby vaginal or cesarean section, outborn or inborn were studied. The study showed that 24% newborn withrespiratory distress required oxygen treatment for less than 24 hours as compared to 76% of the newbornwith respiratory distress.
Keywords: TTN, MAS, RDS,NICU, O2, INSURE,TOF